ACCURACY INVESTIGATION OF THE THREE-POINT RESECTION METHOD THROUGH THE DISTRIBUTION OF CONTROL POINTS ACROSS FOUR QUADRANTS - Sharafeldin Mohamed Osman, Anas; Mabrouk, Abdalla M A; Mahjoub, Abdalraheem M A; Elkhalifa, Eltayeb A M; Abbas Elhag, A (Journal of Marine-Earth Science and Technology, 2021)
The three-point resection method is a valuable and effective technique in surveying that provides accurate and efficient solutions for determining the position of a resected point (point of unknown location). This paper presents a simple and innovative approach to determining the accuracy of the three-point resection problem in surveying. The method involves distributing control points (points of known locations) across four quadrants and computing the coordinates of the resected point (P) several times in order to see which quadrant provides better accuracy. The study investigates the impact of the positions of the control points, either in one quadrant or a combination of quadrants, on the accuracy of the resected point, which is a new contribution to the existing literature. The primary objective of this article is to explore the influence of the distribution of control points in different quadrants on the accuracy of the resected point. Furthermore, the study aims to determine the optimal positions of the three points in terms of their positions in one quadrant or their positions in a combination of quadrants. The relationship between the relative positions of the resected point and other control points, and the accuracy of the resected point is also examined in detail. The results of this study show that the relative positions of the control points and the resected point significantly impact the accuracy of the resected point. The paper concludes by defining the positions of control points distributed across quadrants that result in the best accuracy of the resected point.